2017
DOI: 10.1371/journal.pone.0178834
|View full text |Cite
|
Sign up to set email alerts
|

A matter of months: High precision migration chronology of a Bronze Age female

Abstract: Establishing the age at which prehistoric individuals move away from their childhood residential location holds crucial information about the socio dynamics and mobility patterns in ancient societies. We present a novel combination of strontium isotope analyses performed on the over 3000 year old “Skrydstrup Woman” from Denmark, for whom we compiled a highly detailed month-scale model of her migration timeline. When combined with physical anthropological analyses this timeline can be related to the chronologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 48 publications
4
60
0
Order By: Relevance
“…As an example, Font and colleagues found endogenous Sr to be the most significant contributor to the geospatial signal encoded in the 87 Sr/ 86 Sr of hair, while several other studies conversely found strong relationships between exogenous sources and the 87 Sr/ 86 Sr of hair . Therefore, separating the factors contributing to the 87 Sr/ 86 Sr of hair is paramount for utilizing this analytical tool in anthropologic studies …”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…As an example, Font and colleagues found endogenous Sr to be the most significant contributor to the geospatial signal encoded in the 87 Sr/ 86 Sr of hair, while several other studies conversely found strong relationships between exogenous sources and the 87 Sr/ 86 Sr of hair . Therefore, separating the factors contributing to the 87 Sr/ 86 Sr of hair is paramount for utilizing this analytical tool in anthropologic studies …”
Section: Resultssupporting
confidence: 89%
“…11,47,50 Therefore, separating the factors contributing to the 87 Sr/ 86 Sr of hair is paramount for utilizing this analytical tool in anthropologic studies. 5,6 Comparing the 87 Here, we suggest that the difference in the 87 As our goal in this study was to assess the capacity of the 87 Sr/ 86 Sr ratio of hair to record geographic information, it is important to identify and remove suspected "travelers" from the dataset. To identify suspected "travelers" we excluded leached hair and leachate pairs with a difference in their 87 Sr/ 86 Sr ratios greater than 0.00034 (Δ Hair-Leach ) (Figure 3).…”
Section: Sr-isotope Ratios Of Hairmentioning
confidence: 99%
See 3 more Smart Citations